Makna dan Prosedur Penerjemahan Metafora pada Komik Kureyon Shinchan Volume 1 – 20 Karya Yoshito Usui - Puspa Antari, Ida Ayu Putu (Humanis, 2017)
Metaphor is known as one of interesting phenomenons in linguistic study in which the translator often encounter problems on it’s translation due to language and culture differences. In order to understanding the meaning of metaphor, Larson divided metaphor’s structure into topic, image, and point of similarity. To analyze the translation of methapor that the translator used, according to Newmark, there are seven types of procedures that appliable. They are r eproducing the same image in the target language (TL), r eplac ing the image in the source language ( SL ) with a standard TL image , t ranslation of metaphor by simile , t ranslation of metaphor by simile plus sens e, c onverting metaphor to sense , d eletion , and combining s ame metaphor with sense .